A Co-Citation and Co-Word Analysis of Social Entrepreneurship Research. Issue 3 (2nd September 2022) - Tan Luc, Phan; Xuan Lan, Pham; Nhat Hanh Le, Angelina; Thanh Trang, Bui
Abstract: This article aims to provide the intellectual structure and the evolution of research themes in social entrepreneurship. The authors deploy co-citation and co-word analyses to scrutinise 1278 social entrepreneurship research from the Web of Science database. In the co-citation analysis, five themes in social entrepreneurship are identified. These include the concept development of social entrepreneurship and social enterprise; bricolage and issues related to management in social entrepreneurship; opportunity recognition, motivation and intention; social innovation in social entrepreneurship; and institutional contexts. After that, the co-word analysis is used to comprehend the evolution of each research theme and to uncover potential future research directions. This research contributes to social entrepreneurship literature by combining co-citation analysis and keyword analysis to determine the literature structure and potential research directions.